The Influence Of Accountant Code Of Conduct In Detecting Fraudulent Financial Reporting On Pt Lintas Samudra Jaya - Famia Septa Dinda Alfia; Sri Trisnaningsih (Green Publisher Indonesia, 2022)
This study aims to examine the effect of the Accountant Code of Ethics in detecting fraudulent financial reporting on PT Lintas Samudra Jaya. The subject of this research is PT Lintas Samudra Jaya or LSJ Group which consists of 40 branches in Indonesia. The research method in this study is qualitative descriptive using clear explanations in accordance with empirical conditions that occur in the field. Meanwhile, the research location in this study is one of the companies engaged in providing container and trailer expedition services, using interview, observation and secondary data processing techniques from the company. The conclusion of the study is that the accountant's code of ethics has an effect on the detection of fraudulent financial reporting on PT Lintas Samudra Jaya. It can be proven by interviews with LSJ Group accountants that all LSJ Group accountants are able to have an accountant's code of ethics consisting of responsibility, public interest, integrity, objectivity and independence, prudence, scope and nature of service principles.